Exposed Steel Framing on High Rise Buildings - Nassetta, Anthony F. (Engineering Journal, 1969)
Modern architecture is imposing greater and greater demands on integration and expression of structural materials in building design, and steel is very much a part of this trend. Steel, however, must no longer be considered an assembly of beams and columns forming the supporting framework or "skeleton" of the building, encased in fire protective material. The skeleton is coming out of the closet. Architectural use of exposed steel is growing steadily as more and more design possibilities are explored and adopted. Many buildings in cities throughout this country and Europe have already been designed and constructed using exposed steel framing to varying degrees. It has long been considered by architects and engineers, however, that fire protection is one of the main problems in using exposed steel, particularly in high rise buildings. Much research by AISI, AISC, UL, and ASTM has been accomplished and is still underway, updating fire protection technology to enable proper and safe design by architects and engineers.